AN ASSESSMENT OF THE ETHICAL VALUES OF AL-MUSTAFTI (THE CLIENT) AND ITS IMPLICATIONS TO ISLAMIC EDUCATION IN THE 21st CENTURY NIGERIA - Ladan, Abdulkadir Aliyu (Sokoto Educational Review, 2018)
Fatwa (legal opinion) is a solution proffer to a Mustafti (client). This is in order "to guide him/her in both his spiritual and mundane lives. The interactions between the Mufti (scholar - jurist) and the Mustafti which are either face to face or written require some ethical values to be comprehended and acquired by the Mustaftti. Many occasions especially in public lectures or enlightenment programmes organized in the mosques some audience ask meaningless questions or ask questions on ambiguous matters. Questions of these nature or their likes tend to brew mix- feelings among the audience, especially where their educational attainment Islamically is low. This paper is an elucidation of the ethical values expected of the client to adhere to in the process of his interaction with the Mufti, such as the solution to laxity in the method of approach to problems, etc. Similarly, the implications of such requirements to Nigerian society were discussed i.e. addressing the Mufti with soft tone and humility.